Synthesis, Characterization and Electrochemical Evaluation of Layered Vanadium Phosphates as Cathode Material for Aqueous Rechargeable Zn-ion Batteries - De Luna, Yannis; Bensalah, Nasr (Frontiers in Materials, 2021)
The potential application of rechargeable multivalent ion batteries in portable devices and renewable energy grid integration have gained substantial research interest in aqueous Zn-ion batteries (ZIBs). Compared to Li-based batteries, ZIBs offer lower costs, higher energy density, and safety that make them more attractive for energy storage in grid integration applications. Currently, more research is required to find a suitable cathode material for ZIBs with high capacity and structural stability during charge/discharge cycling. Vanadium phosphate (VOP) compounds as cathode material for ZIBs have been of particular interest, owing to vanadium’s diverse oxidation states. In this present work, two VOP compounds, [H0.6(VO)3(PO4)3(H2O)3].4H2O and VOPO4.2H2O, were synthesized from phosphoric acid and different sources of vanadium via a simple hydrothermal method. Various characterization techniques were carried out, revealing the layered structure of both products and high purity of [H0.6(VO)3(PO4)3(H2O)3].4H2O. Zn/VOP batteries were prepared using Zn metal as counter and reference electrode and 3 M ZnSO4.7H2O as electrolyte. Electrochemical tests were conducted to evaluate the cycling performance of VOPs as cathode material for aqueous Zn-ion batteries. Based on the results, both compounds have shown highly reversible Zn-ion intercalation and deintercalation. VOPO4.2H2O achieved a higher specific capacity of up to 85 mAh/g during discharging, as opposed to 65 mAh/g for the hydrated VOP complex. However, [H0.6(VO)3(PO4)3(H2O)3].4H2O is more stable with higher reproducibility than VOPO4.2H2O during cycling. Nevertheless, more research is still required to enhance the specific capacity and improve the cycling performance of VOP-based cathodes for their prospective use in aqueous ZIBs.